Existence and Multiplicity Results of Homoclinic Solutions for the DNLS Equations with Unbounded Potentials - Defang Ma; Zhan Zhou (Abstract and Applied Analysis)
A class of difference equations which include discrete nonlinear Schrödinger equations as special cases are considered. New sufficient conditions of the existence and multiplicity results of homoclinic solutions for the difference equations are obtained by making use of the mountain pass theorem and the fountain theorem, respectively. Recent results in the literature are generalized and greatly improved.